Country data on AMR in Pakistan in the context of community-acquired respiratory tract infections: links between antibiotic susceptibility, local and international antibiotic prescribing guidelines, access to medicine and clinical outcome. (6th September 2022) - Torumkuney, Didem; Jamil, Bushra; Nizamuddin, Summiya; van Hasselt, James; Pirzada, Uzma; Manenzhe, Rendani
Abstract: Background: Antimicrobial resistance (AMR) is one of the biggest threats to global public health. Selection of resistant bacteria is driven by inappropriate use of antibiotics, amongst other factors. COVID-19 may have exacerbated AMR due to unnecessary antibiotic prescribing. Country-level knowledge is needed to understand options for action. Objectives: To review the current situation with respect to AMR in Pakistan and initiatives addressing it. Identifying areas where more information is required will provide a call to action to minimize any further rises in AMR and improve patient outcomes. Methods: National AMR initiatives, antibiotic use and prescribing in Pakistan, and availability of susceptibility data, in particular for the key community-acquired respiratory tract infection (CA-RTI) pathogens ( Streptococcus pneumoniae and Haemophilus influenzae ) were identified. National and international antibiotic prescribing guidelines for specific CA-RTIs (community-acquired pneumonia, acute otitis media and acute bacterial rhinosinusitis) commonly used locally were also reviewed, plus local antibiotic availability. Insights from a local clinician and clinical microbiologist were sought to contextualize this information. Conclusions: Pakistan is active in developing initiatives to address AMR such as compiling a National Action Plan. However, antibiotic consumption is high and although there is legislation in place prohibiting over-the-counter purchase of antibiotics, this is still possible. Healthcare professionals use local and international antibiotic prescribing guidelines for CA-RTIs when managing patients. As highlighted by the clinical microbiologist's expert comments, surveillance of AMR in locally prevalent microorganisms is lacking. A more standardized inclusive approach in developing local guidelines, using up-to-date local surveillance data of isolates from community-acquired infections, could make management guideline use more locally relevant for clinicians. This would pave the way for a higher level of appropriate antibiotic prescribing and improved adherence. This would, in turn, potentially limit AMR development and improve clinical outcomes for patients.